Management of Ankyloglossia with different severity: a case series in dental surgery - Christianto, Stephanus; Priyanto, Winarno; Sjamsudin, Endang (Universitas Padjadjaran, 2024)
Introduction: The lingual frenulum is an important oral structure that plays an important role in the act of suction, speech, and feeding. Ankyloglossia (tongue tie) is a congenital anomaly that results when lingual frenulum is too short and adhere to tip of tongue, limiting the tongue movement. This case report aimed to explain management of Ankyloglossia with different severity. Case Report: This case report reported three cases of ankyloglossia with different ages and complaints of difficulty in feeding and speech. The patients were treated for lingual frenectomy procedure under general anesthesia using one haemostats method. The haemostats were used to clamp the upper aspect of frenulum which might have been helpful to guide the incision close to ventral surface of tongue. Care had to be taken not to injure the submandibular ducts when making incision at lower part of tongue. The result after 1 week of surgery: the wound was completely healed. Conclusion: Ankyloglossia will impair the function of suction, speech and feeding that affecting a considerable number of infants and children. It is important that accurate information and guidance are given to parents with regard to the indications and potential benefit of tongue tie revision. These case series offer guidelines which can be used by general and pediatric dentist for examination, diagnosis and treatment of ankyloglossia in different severity.KeywordAnkyloglossia, congenital, lingual frenulum